Enhancing Data and Communication Security with Key Recovery Technology - Chankulchorn, Jumroon; Kanyamee, Kanokwan (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
In the digital era, network-based communication has become a cornerstone of diverse human and societal activities. This evolution has brought to the forefront the critical importance of information security and communication reliability. To protect sensitive data from threats that could compromise its integrity and availability, Key Recovery Technology (KRT) plays a pivotal role in enhancing trust and resilience in digital communication systems. It is particularly essential in cases where secret keys used for data encryption are lost or become unusable, which can result in a complete loss of access to encrypted information. Such incidents may result in significant damage at individual, organizational, and infrastructural levels, including the loss of business-critical evidence, breaches of personal data, or the disruption of essential public services. KRT enables the recovery of secret keys in a secure and privacy-preserving manner, ensuring that data remains accessible without violating user confidentiality. Moreover, this technology supports compliance with legal and regulatory frameworks by allowing authorized access to data under investigation, ensuring transparency and accountability while preventing unauthorized access. Therefore, KRT serves as a key enabler of robust information security, supporting business continuity and fostering sustainable trust in the digital ecosystem by upholding the principles of confidentiality, integrity, and user privacy.